Measuring the Coulombic Efficiency of Lithium Metal Cycling in Anode-Free Lithium Metal Batteries. Issue 14 (1st January 2018) - Genovese, Matthew; Louli, A. J.; Weber, Rochelle; Hames, Sam; Dahn, J. R.
Abstract : Anode-free or zero excess lithium metal batteries (LMBs) have the potential for very high energy density, but are plagued by extremely short cycle life due to low lithium metal cycling efficiency. As more researchers report on the anode-free configuration and methods to improve performance, it is important to understand how to properly measure and interpret the performance metrics from these cells. Herein, we describe the cycling of high voltage NMC 532 || Cu anode-free lithium metal pouch cells using an ultra-high-precision-charger (UHPC). The cells were cycled under low and high applied pressure with two different electrolyte formulations. Changing the lower cutoff voltage of these cells from 3.6 V to 1.25 V significantly affects their capacity retention and coulombic efficiency. The cells discharged to 3.6 V show a high initial CE (>99.8%) which rapidly declines after 5–10 cycles and stabilizes at a much lower value (<99%). This behavior is attributed to the irreversible capacity of the NMC cathode which is not recovered on the 3.6V discharge and remains as excess lithium on the anode. This excess lithium artificially inflates the CE until it's depleted and the true cell performance is quickly revealed. By contrast, the cells discharged to 1.25 V show linear capacity fade at a constant CE < 99%. Thus, anode-free cells can offer rapid feedback on the true lithium metal cycling behavior in a full cell configuration making them effective tools for evaluating strategies to improve lithium metal cycling performance.